2015
DOI: 10.1007/s00405-015-3729-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nasoseptal flap elevation on sinonasal quality of life in endoscopic endonasal approach to pituitary adenomas

Abstract: To evaluate the impact of nasoseptal flap (NSF) elevation on sinonasal quality of life (QOL) in patients with pituitary adenomas who underwent endoscopic endonasal trans-sphenoidal approach (EETSA), the data of 106 eligible patients were included from February 2011 to December 2014. The scores of Sinonasal Outcome Test (SNOT-22) Questionnaire were assessed in case (that received reconstruction with NSF) and control groups preoperatively as well as 1, 3, 6, and more than 12 months postoperatively. Nine most rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
2
46
1
Order By: Relevance
“…Correspondingly, Jalessi et al demonstrated that in patients with pituitary adenomas undergoing endoscopic endonasal transsphenoidal surgery, NSF harvest resulted in a transient decrease in QOL that returned to baseline within 3 months. Overall, there was significant improvement in SNOT‐22 scores at 12 months after surgery compared to preoperative data …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Correspondingly, Jalessi et al demonstrated that in patients with pituitary adenomas undergoing endoscopic endonasal transsphenoidal surgery, NSF harvest resulted in a transient decrease in QOL that returned to baseline within 3 months. Overall, there was significant improvement in SNOT‐22 scores at 12 months after surgery compared to preoperative data …”
Section: Discussionmentioning
confidence: 81%
“…Overall, there was significant improvement in SNOT-22 scores at 12 months after surgery compared to preoperative data. 33 Examining QOL in extended endonasal approaches with NSF reconstruction for benign skull base tumors, Georgalas et al demonstrated limited impact, which was mostly related to headache and reduced olfaction utilizing the Rhinosinusitis Outcome Measure-31 questionnaire. 34 Harvey et al found that sinonasal QOL was more closely related to skull base pathology compared to NSF use, suggesting that loss of sinonasal function from radiation or resection of functional areas including olfactory mucosa played a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we focused on studies of subjective olfaction after ESBS in the sella/parasella (Table ). Again, four of the seven studies found no long‐term (beyond 3 months) postoperative changes in subjective olfaction . Three studies found significantly worse postoperative olfaction using a subjective VAS .…”
Section: Discussionmentioning
confidence: 89%
“…Jalessi et al compared NSF reconstructions in ESBS to other types of fat or fascial grafts. They did find a transient deficit in postoperative olfaction at 1 month, but this was only in the NSF group, and it went on to return to baseline by 3 months . In contrast, Kim et al utilized bilateral rescue flaps for skull base reconstruction as opposed to NSF, and did find a significant worsening in subjective olfaction measured using a study‐specific VAS …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation